STRATEGY FOR TEACHERS TO SUPPORT SELF-REGULATION FOR STUDENT LEARNING PROCESS IN POST-PANDEMIC LEARNING - Lini Oltiovini Udju; Yulia Setia; Ivy Mary Lin (Universitas Kristen Petra, 2024)
Christian education aims to form students who have Christ-like qualities. This effort is a mission that Christian education wants to achieve. To develop these qualities, students need good self-regulation skills in learning. Self-regulation is the ability of students to direct their thoughts, feelings, and behavior to achieve learning goals. Students who have good self-regulation will achieve success in learning. However, since post-pandemic learning, students have had challenges adapting from online learning to face-to-face learning. This affects student self-regulation in learning. Therefore, Christian teachers, as shepherds, have a responsibility to help students experience increased self-regulation. In this study, researchers wanted to examine the strategies used by a teacher to support student self-regulation in the post-pandemic learning context. This study uses descriptive qualitative research methods with observation and interviews as data collection techniques. The data were then analyzed using data reduction, presentation, and conclusion. After examining more deeply, the researchers found that the teacher implemented several essential strategies in the context of post-pandemic learning and were proven to support students in experiencing increased self-regulation abilities in the learning process.